The Institutional Determinants of Bilateral Trade Patterns - Henri L.F. De Groot; Gert-Jan Linders; Piet Rietveld; Uma Subramanian (European Regional Science Association (ERSA), 2003)
The intensity of international transactions remains lower than could be potentially justified on the basis of transportation costs alone. This has become known as the ?mystery of the missing trade?. Transaction costs may be responsible for ?under-trading? across national borders. More specifically, the relatively low intensity of foreign trade may reflect the importance of institutions for cross-border transactions. This paper studies the effect of institutions on trade flows, using a gravity model approach. According to the gravity model, trade between any two countries is a function of each country's gross domestic product, the distance between them, and possibly other variables that reflect the costs of trade between them. We start from a standard gravity equation that incorporates variables for geographical proximity, common language, trade policy and common history. These factors reflect costs of trade across geographical and cultural distances. The quality of governance and the extent of familiarity with the resulting framework of rules and norms also affect the costs of doing business between any pair of countries. The effects of institutional quality and similarity on transaction costs may be substantial in international markets. Because of the greater extent of competition and higher uncertainty in international markets, the impact of quality and similarity of institutions on cross-border trade may be relatively pronounced. Therefore, this paper extends the gravity equation to include proxies for institutional quality and institutional homogeneity between trade partners. We use indicators on political stability, regulatory quality, corruption and other proxies that reflect the quality of governance, available from the comparative data set constructed by Kaufmann and others (World Bank, 2002). Variables that capture similarity in the quality of institutions are then constructed from these indicators. We test whether institutional homogeneity and institutional quality have an independent impact on trade volume between pairs of countries. The results indicate that, for example, having a similar law or regulatory framework promotes bilateral trade. Furthermore, a better quality of formal institutions on average coincides with higher trade. JEL codes: F14 Keywords: bilateral trade flows, gravity model, institutions
Keywords: 330